A chemically amplified positive ultraviolet photoresist and its preparation and use method

By using crosslinking agents in ultraviolet photoresist to catalyze polymer chains to form a network structure, the cracking problem of positive ultraviolet photoresist in the thickness range of 10 to 30 μm is solved, and its passivation layer in the back section of the integrated circuit is improved. or applications of high-energy injection processes.

CN113671793BActive Publication Date: 2024-12-31XUZHOU B&C CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202110982014.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-08-25
Publication Date
2024-12-31
Estimated Expiration
2041-08-25

AI Technical Summary

Technical Problem

The prior art is difficult to effectively solve the cracking problem of chemically amplified positive UV photoresist at a thickness of 10 to 30 μm, which affects its application in the back section of the integrated circuit or high-energy injection process.

Method used

Chemically amplified positive UV photoresist formulas including the first and second polypara styrene-based polymer resins, photoacid generators, acid quenchers, crosslinkers, levelers and solvents, and The polymer chain is catalyzed in advance by heat-baking by crosslinking agent to form a network structure, thereby improving the cured material brittle defect of the photoresist.

Benefits of technology

Effectively solve the cracking problem of positive thick film ultraviolet photoresist, especially in the thickness range of 10 to 30 μm, improve the strength and stability of the photoresist, expand its passivation layer or high-energy injection process in the back section of the integrated circuit. scope of application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113671793B_ABST
    Figure CN113671793B_ABST
Patent Text Reader

Abstract

The present invention relates to a chemically amplified positive ultraviolet photoresist and a preparation and use method thereof. The photoresist comprises the following components in mass percentage: 25-45% poly(p-hydroxystyrene) polymer resin; 0.5-1.5% photoacid generator; 0.1-0.2% acid quencher; 2-4% crosslinker; 0.1-0.5% leveling agent; 48.8-72.3% solvent. The preparation method comprises the following steps: mixing the components of the chemically amplified positive ultraviolet photoresist. The use method comprises the following steps: coating the chemically amplified positive ultraviolet photoresist on a silicon wafer, and sequentially performing pre-baking, exposure, post-baking and development. The present invention solves the problem of photoresist cracking, especially the cracking problem of positive thick film (10-30 μm) photoresist, is suitable for the back-end passivation layer of integrated circuits or high-energy injection processes, and expands the scope of application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photoresists, and in particular to a chemically amplified positive ultraviolet photoresist and a preparation and use method thereof. Background Art

[0002] I-line thick film photoresist with a thickness close to or greater than 20μm is often used in the back-end passivation protection layer or high-energy implantation process of integrated circuits. However, a common problem encountered during research and use is the cracking of the film, which seriously affects the promotion and application. In order to solve this problem, people have made many efforts.

[0003] For example, polyol active diluents are used to improve coating cracking in US Pat. No. 6,716,568. Small molecule active diluents are used to improve coating cracking in US Pat. No. 5,102,772, such as XD7342 and CY179.

[0004] Jiangsu Handuo Optical Materials Co., Ltd.'s Chinese patent CN108132584B "A photoresist composition comprising polyparahydroxystyrene polymers and acrylate copolymers" solves the cracking problem of acrylate-based photoresists when the thickness is greater than or equal to 6μm by increasing the molecular weight of the acrylate copolymer and improving the flexibility of the acrylate copolymer molecular chain, and blending the acrylate copolymer with traditional polyparahydroxystyrene polymers.

[0005] However, the above patent cannot achieve satisfactory results in solving the cracking problem of positive thick film (10-30 μm) ultraviolet photoresist. Summary of the invention

[0006] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and provide a chemically amplified positive ultraviolet photoresist which can effectively solve the problem of cracking of chemically amplified positive ultraviolet photoresist and its preparation and use method.

[0007] In order to achieve the purpose of the present invention, this application provides the following technical solutions.

[0008] In a first aspect, the present application provides a chemically amplified positive ultraviolet photoresist, wherein the photoresist comprises the following components in percentage by mass:

[0009]

[0010] In one embodiment of the first aspect, the poly(p-hydroxystyrene) polymer resin comprises a first poly(p-hydroxystyrene) polymer resin and a second poly(p-hydroxystyrene) polymer resin;

[0011] The first poly(p-hydroxystyrene) polymer resin includes a first poly(p-hydroxystyrene) and / or a derivative of the first poly(p-hydroxystyrene), wherein the first poly(p-hydroxystyrene) is a copolymer of p-hydroxystyrene, styrene and tert-butyl acrylate, and the derivative of the first poly(p-hydroxystyrene) includes one or more of a tert-butyloxycarbonyl-protected first poly(p-hydroxystyrene), a tert-butyl-protected first poly(p-hydroxystyrene), an acetal-protected first poly(p-hydroxystyrene) and a ketal-protected first poly(p-hydroxystyrene);

[0012] The second poly-p-hydroxystyrene polymer resin is a copolymer of p-hydroxystyrene, styrene and p-methoxystyrene.

[0013] In one embodiment of the first aspect, the mass percentage of the first poly(p-hydroxystyrene) polymer resin is 5-15%, and the mass percentage of the second poly(p-hydroxystyrene) polymer resin is 20-30%.

[0014] In one implementation of the first aspect, the photoresist further includes at least one of the following technical features:

[0015] 1a) the first poly(p-hydroxystyrene) polymer resin is ST25 from Jiangsu Handuo Optical Materials Co., Ltd.;

[0016] 1b) the weight average molecular weight of the first poly(p-hydroxystyrene) polymer resin is 20,000 to 30,000;

[0017] 1c) the molecular weight distribution coefficient of the first poly(p-hydroxystyrene) polymer resin is 1.5 to 3.5;

[0018] 1d) the second poly(p-hydroxystyrene) polymer resin is S601 from Jiangsu Handuo Optical Materials Co., Ltd.;

[0019] 1e) the weight average molecular weight of the second poly(p-hydroxystyrene) polymer resin is 6000 to 18000;

[0020] 1f) The molecular weight distribution coefficient of the second poly(p-hydroxystyrene) polymer resin is 1.5 to 2.5.

[0021] In one implementation of the first aspect, the photoresist further includes at least one of the following technical features:

[0022] 2a) the photoacid generator is at least one selected from N-hydroxynaphthoimide trifluoromethanesulfonic acid, (4,8-dihydroxy-1-naphthyl)dimethylsulfonium trifluoromethanesulfonate, (4,7-dihydroxy-1-naphthyl)dimethylsulfonium trifluoromethanesulfonate, (4-methoxynaphthyl)diphenylsulfonium trifluoromethanesulfonate, (4-phenylthiophenyl)diphenylsulfonium trifluoromethanesulfonate, 2-(benzo[d][1,3]dioxolan-5-yl)-4,6-bis(trichloromethyl)-1,3,5-triazine, 2-(2,4-dimethoxyphenyl)-4,6-bis(trichloromethyl)-1,3,5-triazine and 2-[4-(4-methoxyphenyl)phenyl]-4,6-bis(trichloromethyl)-1,3,5-triazine;

[0023] 2b) the acid quencher is at least one selected from triethylamine, tributylamine, trioctylamine and tri(3,6-dioxaheptyl)amine;

[0024] 2c) the cross-linking agent is selected from at least one of diethylene glycol divinyl ether, tetramethoxymethyl glycoluril and hexamethoxymethyl melamine;

[0025] 2d) the leveling agent is selected from at least one of 3M fluorocarbon surfactant FC-4430 and Troysol S366;

[0026] 2e) the solvent is selected from at least one of anisole, toluene, xylene, trimethylolbenzene, chlorobenzene, dichlorobenzene, propylene glycol monoacetate, propylene glycol methyl ether acetate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, diethylene glycol methyl ether, diethylene glycol ethyl ether, diethylene glycol methyl ethyl ether, butyl acetate, neopentyl acetate, methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, cyclohexanone, diacetone alcohol, gamma-butyrolactone and ethyl lactate.

[0027] In a second aspect, the present application also provides a method for preparing the chemically amplified positive ultraviolet photoresist as described above, the preparation method comprising the following steps: mixing the polyparahydroxystyrene polymer resin, the photoacid generator, the acid quencher, the cross-linking agent, the leveling agent and the solvent in proportion to obtain the chemically amplified positive ultraviolet photoresist.

[0028] In one embodiment of the second aspect, after all raw materials are mixed, the preparation method includes filtering.

[0029] In one embodiment of the second aspect, the filter pore size is 1 to 5 μm.

[0030] In a third aspect, the present application also provides a method for using the chemically amplified positive ultraviolet photoresist as described above, the method comprising the following steps:

[0031] The chemically amplified positive ultraviolet photoresist is coated on a silicon wafer, and sequentially subjected to pre-baking, exposure, post-baking and development to obtain a photolithographic pattern.

[0032] In one implementation of the third aspect, the method of use further includes at least one of the following technical features:

[0033] 3a) The pre-baking temperature is 70-130°C;

[0034] 3b) Pre-baking time is 3 to 7 minutes;

[0035] 3c) The exposure machine used for the exposure is an LED 365nm contact exposure machine;

[0036] 3d) Exposure energy is 200~500mJ / cm 2 ;

[0037] 3e) post-baking temperature is 70-130°C;

[0038] 3f) Post-baking time is 1 to 3 minutes;

[0039] 3g) the developing solution used in the developing comprises tetramethylammonium hydroxide;

[0040] 3h) The development time is 1 to 5 minutes.

[0041] Compared with the prior art, the present invention has at least one of the following beneficial effects:

[0042] (1) The chemically amplified positive ultraviolet photoresist of the present invention includes a crosslinking agent, which is pre-heated and catalytically crosslinked during use to form a network structure of the polymer chain locally, thereby improving the brittle cracking defect of the photoresist cured product;

[0043] (2) The present invention is completed without changing the main raw material formula of the original chemically amplified positive ultraviolet photoresist (which can only meet the requirement that the photoresist does not crack when the coating thickness is less than 10 μm), and only adds a cross-linking agent;

[0044] (3) The chemically amplified positive ultraviolet photoresist of the present invention solves the problem of cracking of chemically amplified positive ultraviolet photoresist, especially the cracking problem of positive thick film (10-30 μm) ultraviolet photoresist;

[0045] (4) The photoresist coating film of the present invention has a thickness of about 10 to 30 μm, which is suitable for the back-end passivation layer of integrated circuits or high-energy injection processes, thus expanding the scope of application. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 This is a thick film image of the photoresist prepared in Example 1 after use.

[0047] Figure 2This is a thick film image of the photoresist prepared in Comparative Example 1 after use.

[0048] Figure 3 This is a thick film image of the photoresist prepared in Example 2 after use.

[0049] Figure 4 This is a thick film image of the photoresist prepared in Example 3 after use.

[0050] Figure 5 This is a thick film image of the photoresist prepared in Example 4 after use.

[0051] Figure 6 This is a thick film image of the photoresist prepared in Example 5 after use. DETAILED DESCRIPTION

[0052] Unless otherwise indicated, implied from the context, or customary in the prior art, all parts and percentages in this application are based on weight, and the test and characterization methods used are all current as of the filing date of this application. Where applicable, the contents of any patent, patent application or publication referred to in this application are fully incorporated herein by reference, and their equivalent patent families are also incorporated by reference, especially the definitions of synthesis techniques, product and processing designs, polymers, comonomers, initiators or catalysts disclosed in these documents in the art. If the definition of a specific term disclosed in the prior art is inconsistent with any definition provided in this application, the definition of the term provided in this application shall prevail.

[0053] Numerical ranges in this application are approximate values, so unless otherwise specified, they may include values ​​outside the range. Numerical ranges include all values ​​from the lower limit to the upper limit increased by 1 unit, provided that there is an interval of at least 2 units between any lower value and any higher value. For example, if the recorded component, physical or other properties (such as molecular weight, melt index, etc.) are 100 to 1000, it means that all single values ​​are clearly listed, such as 100, 101, 102, etc., and all sub-ranges, such as 100 to 166, 155 to 170, 198 to 200, etc. For a range comprising a value less than 1 or comprising a fraction greater than 1 (such as 1.1, 1.5, etc.), 1 unit is appropriately regarded as 0.0001, 0.001, 0.01 or 0.1. For ranges containing single digit numbers less than 10 (e.g., 1 to 5), 1 unit is generally considered to be 0.1. These are only specific examples of what is intended, and all possible combinations of numerical values ​​between the lowest and highest values ​​recited are considered to be expressly stated in this application. The numerical ranges within this application provide, among other things, calcium-containing filler content, stirring temperature, and various features and properties of these components.

[0054] When used with respect to chemical compounds, unless expressly specified otherwise, the singular includes all isomeric forms and vice versa (e.g., "hexane" includes all isomers of hexane, individually or collectively). In addition, nouns using "a," "an," or "the" also include their plural forms unless expressly specified otherwise.

[0055] The terms "comprising", "including", "having" and their derivatives do not exclude the presence of any other components, steps or processes, and are irrelevant to whether these other components, steps or processes are disclosed in this application. To eliminate any doubt, unless explicitly stated, all compositions using the terms "comprising", "including", or "having" in this application may include any additional additives, adjuvants or compounds. On the contrary, except for those necessary for operating performance, the term "essentially consisting of..." excludes any other components, steps or processes from the scope of any description of the term below. The term "consisting of..." does not include any components, steps or processes that are not specifically described or listed. Unless explicitly stated, the term "or" refers to the listed individual members or any combination thereof.

[0056] The first aspect of the present invention provides a chemically amplified positive ultraviolet photoresist, comprising the following components in mass percentage:

[0057]

[0058]

[0059] Preferably, the poly(p-hydroxystyrene) polymer resin comprises a first poly(p-hydroxystyrene) polymer resin and a second poly(p-hydroxystyrene) polymer resin;

[0060] The first poly(p-hydroxystyrene) polymer resin includes a first poly(p-hydroxystyrene) and / or a derivative of the first poly(p-hydroxystyrene), wherein the first poly(p-hydroxystyrene) is a copolymer of p-hydroxystyrene, styrene and tert-butyl acrylate, and the derivative of the first poly(p-hydroxystyrene) includes one or more of a tert-butyloxycarbonyl-protected first poly(p-hydroxystyrene), a tert-butyl-protected first poly(p-hydroxystyrene), an acetal-protected first poly(p-hydroxystyrene) and a ketal-protected first poly(p-hydroxystyrene);

[0061] The second poly-p-hydroxystyrene polymer resin is a copolymer of p-hydroxystyrene, styrene and p-methoxystyrene.

[0062] More preferably, the mass percentage of the first poly(p-hydroxystyrene) polymer resin is 5-15%, such as 5-11% or 11-15%, and the mass percentage of the second poly(p-hydroxystyrene) polymer resin is 20-30%, such as 20-26.5% or 26.5-30%.

[0063] Preferably, it also includes at least one of the following technical features:

[0064] 1a) the first poly(p-hydroxystyrene) polymer resin is ST25 from Jiangsu Handuo Optical Materials Co., Ltd.;

[0065] 1b) the weight average molecular weight of the first poly(p-hydroxystyrene) polymer resin is 20,000 to 30,000, such as 20,000 to 25,700 or 25,700 to 30,000;

[0066] 1c) the molecular weight distribution coefficient of the first poly(p-hydroxystyrene) polymer resin is 1.5 to 3.5, such as 1.5 to 2.3 or 2.3 to 3.5;

[0067] 1d) the second poly(p-hydroxystyrene) polymer resin is S601 from Jiangsu Handuo Optical Materials Co., Ltd.;

[0068] 1e) the weight average molecular weight of the second poly(p-hydroxystyrene) polymer resin is 6000-18000, such as 6000-13200 or 13200-18000;

[0069] 1f) The molecular weight distribution coefficient of the second poly(p-hydroxystyrene) polymer resin is 1.5 to 2.5, such as 1.5 to 2.2 or 2.2 to 2.5.

[0070] Preferably, it also includes at least one of the following technical features:

[0071] 2a) The photoacid generator is selected from N-hydroxynaphthoimide trifluoromethanesulfonic acid (PAG 1), (4,8-dihydroxy-1-naphthyl)dimethylsulfonium trifluoromethanesulfonate (PAG 2), (4,7-dihydroxy-1-naphthyl)dimethylsulfonium trifluoromethanesulfonate (PAG 3), (4-methoxynaphthyl)diphenylsulfonium trifluoromethanesulfonate (PAG 4), (4-phenylthiophenyl)diphenylsulfonium trifluoromethanesulfonate (PAG 5), 2-(benzo[d][1,3]dioxolan-5-yl)-4,6-bis(trichloromethyl)-1,3,5-triazine (PAG 6), 2-(2,4-dimethoxyphenyl)-4,6-bis(trichloromethyl)-1,3,5-triazine (PAG 7), 7) and at least one of 2-[4-(4-methoxyphenyl)phenyl]-4,6-bis(trichloromethyl)-1,3,5-triazine (PAG 8);

[0072] The structural formula is as follows:

[0073]

[0074] 2b) the acid quencher is at least one selected from triethylamine, tributylamine, trioctylamine and tri(3,6-dioxaheptyl)amine;

[0075] 2c) the cross-linking agent is selected from at least one of diethylene glycol divinyl ether, tetramethoxymethyl glycoluril and hexamethoxymethyl melamine;

[0076] 2d) the leveling agent is selected from at least one of 3M fluorocarbon surfactant FC-4430 and Troysol S366;

[0077] 2e) the solvent is selected from at least one of anisole, toluene, xylene, trimethylolbenzene, chlorobenzene, dichlorobenzene, propylene glycol monoacetate, propylene glycol methyl ether acetate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, diethylene glycol methyl ether, diethylene glycol ethyl ether, diethylene glycol methyl ethyl ether, butyl acetate, neopentyl acetate, methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, cyclohexanone, diacetone alcohol, gamma-butyrolactone and ethyl lactate.

[0078] The crosslinking agent in the chemically amplified positive ultraviolet photoresist of the present invention is conducive to forming a long-chain network with the poly(p-hydroxystyrene) polymer resin, and the structural strength is large. The photoresist is not easy to crack, especially the positive thick film (10-30 μm) ultraviolet photoresist is not easy to crack.

[0079] The second aspect of the present invention provides a method for preparing the above-mentioned chemically amplified positive ultraviolet photoresist, comprising the following steps: mixing the poly(p-hydroxystyrene) polymer resin, the photoacid generator, the acid quencher, the cross-linking agent, the leveling agent and the solvent in proportion to obtain the chemically amplified positive ultraviolet photoresist.

[0080] Preferably, after all the raw materials are mixed, the preparation method includes filtering, such as filtering using a microporous membrane filter.

[0081] More preferably, the filter pore size is 1-5 μm, such as 1-3 μm or 3-5 μm.

[0082] The third aspect of the present invention provides a method for using the chemically amplified positive ultraviolet photoresist, comprising the following steps: coating the chemically amplified positive ultraviolet photoresist on a silicon wafer, and sequentially performing pre-baking, exposure, post-baking and development to obtain a photolithography pattern.

[0083] Preferably, it also includes at least one of the following technical features:

[0084] 3a) the pre-baking temperature is 70-130°C, such as 70-100°C or 100-130°C; preferably 130°C;

[0085] 3b) pre-baking time is 3 to 7 minutes, such as 3 to 5 minutes or 5 to 7 minutes; preferably 5 minutes;

[0086] 3c) The exposure machine used for the exposure is an LED 365nm contact exposure machine;

[0087] 3d) Exposure energy is 200~500mJ / cm 2 , such as 200~350mJ / cm 2 or 350~500mJ / cm 2 ; preferably 350mJ / cm 2 ;

[0088] 3e) post-baking temperature is 70-130°C, such as 70-110°C or 110-130°C; preferably 110°C;

[0089] 3f) post-baking time is 1 to 3 minutes, such as 1 to 2 minutes or 2 to 3 minutes; preferably 2 minutes;

[0090] 3g) the developing solution used in the developing comprises tetramethylammonium hydroxide;

[0091] 3h) The developing time is 1 to 5 min, such as 1 to 3 min or 3 to 5 min; preferably 3 min.

[0092] In the present invention, the equipment and raw materials used can be purchased from the market or are commonly used in the art. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.

[0093] The first poly(p-hydroxystyrene) polymer resin grade ST25 used in the following examples and comparative examples is obtained by the following synthesis method:

[0094] Under nitrogen protection, 97.2 g of 4-acetoxystyrene (ASM), 20.6 g of styrene (ST) and 25.4 g of tert-butyl acrylate (TBA) were added to a 500 ml four-necked flask in sequence, and then 3.8 g of initiator azobisisobutyronitrile (AIBN) was added, tetrahydrofuran was used as solvent, and then reacted at 65-70°C for 18 hours. After the reaction product was deprotected, a 4-hydroxystyrene-styrene-butyl acrylate terpolymer was obtained, and its weight average molecular weight M w is 25.7K, and its molecular weight distribution coefficient M w / M n is 2.3.

[0095] The second poly(p-hydroxystyrene) polymer resin grade S601 used in the following examples and comparative examples is obtained by the following synthesis method:

[0096] Under nitrogen protection, 269.9 g of 4-acetoxystyrene (ASM), 9.0 g of styrene (ST) and 2.1 g of p-methoxystyrene (MOST) were added to a 1000 ml four-necked flask in sequence, and then 22.2 g of initiator azobisisobutyronitrile (AIBN) was added, tetrahydrofuran was used as solvent, and then reacted at 65-70°C for 18 hours. After the reaction product was deprotected, a 4-hydroxystyrene-styrene-p-methoxystyrene terpolymer was obtained, and its weight average molecular weight M w is 13.2K, and its molecular weight distribution coefficient M w / M n is 2.2.

[0097] Example

[0098] The embodiments of the present invention will be described in detail below. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.

[0099] Example 1

[0100] A chemically amplified positive ultraviolet photoresist comprises the following components in parts by weight (total 100 parts):

[0101]

[0102] The preparation process of the photoresist is as follows: add each component according to the formula, stir until completely dissolved, and filter through a 1 μm pore size polypropylene (PP) microporous filter membrane to complete the preparation of the photoresist.

[0103] The prepared photoresist is used as follows:

[0104] Spin coating on a 4-inch silicon wafer, pre-bake at 130°C for 5 minutes, and then expose in an LED 365nm contact exposure machine with an exposure energy of 350mJ / cm 2 , then post-baked at 110° C. for 2 minutes, and then developed, wherein the developing time is 3 minutes, and the developer is a tetramethylammonium hydroxide aqueous solution with a concentration of 2.38%.

[0105] The photolithographic pattern is obtained as Figure 1 As shown, the film thickness is 20.2 μm, and the cracking of the coating film is observed by optical developing microscope OM. The specific results are shown in Table 1.

[0106] Comparative Example 1

[0107] A chemically amplified positive ultraviolet photoresist comprises the following components in parts by weight (total 100 parts):

[0108]

[0109] The preparation method of the above-mentioned photoresist is the same as that of Example 1, and the use method of the above-mentioned photoresist is the same as that of Example 1.

[0110] The obtained photolithographic pattern is Figure 2 As shown in the figure (the black line is the cracking area), the film thickness is 20.0μm, and the cracking of the coating film is observed through the optical developing microscope OM. The specific results are shown in Table 1.

[0111] Example 2

[0112] A chemically amplified positive ultraviolet photoresist comprises the following components in parts by weight (total 100 parts):

[0113]

[0114] The preparation method of the above-mentioned photoresist is the same as that of Example 1, and the use method of the above-mentioned photoresist is the same as that of Example 1.

[0115] The obtained photolithographic pattern is Figure 3 As shown, the film thickness is 20.1 μm, and the cracking of the coating film is observed by optical developing microscope OM. The specific results are shown in Table 1.

[0116] Example 3

[0117] A chemically amplified positive ultraviolet photoresist comprises the following components in parts by weight (total 100 parts):

[0118]

[0119] The preparation method of the above-mentioned photoresist is the same as that of Example 1, and the use method of the above-mentioned photoresist is the same as that of Example 1.

[0120] The obtained photolithographic pattern is Figure 4 As shown, the film thickness is 20.0 μm, and the cracking of the coating film is observed by optical developing microscope OM. The specific results are shown in Table 1.

[0121] Example 4

[0122] A chemically amplified positive ultraviolet photoresist comprises the following components in parts by weight (total 100 parts):

[0123]

[0124] The preparation process of the photoresist is as follows: add each component according to the formula, stir until completely dissolved, and filter through a 5 μm pore size polypropylene (PP) microporous filter membrane to complete the preparation of the photoresist.

[0125] The prepared photoresist is used as follows:

[0126] Spin coating on a 4-inch silicon wafer, then pre-bake at 70°C for 7 minutes, and then expose in an LED 365nm contact exposure machine with an exposure energy of 500mJ / cm 2 , then post-baked at 130° C. for 1 minute, and then developed, wherein the developing time is 5 minutes, and the developer is a tetramethylammonium hydroxide aqueous solution with a concentration of 2.38%.

[0127] The photolithographic pattern is obtained as Figure 5 As shown, the film thickness is 30.0 μm, and the cracking of the coating film is observed by optical developing microscope OM. The specific results are shown in Table 1.

[0128] Example 5

[0129] A chemically amplified positive ultraviolet photoresist comprises the following components in parts by weight (total 100 parts):

[0130]

[0131] The preparation process of the photoresist is as follows: add each component according to the formula, stir until completely dissolved, and filter through a 3 μm pore size polypropylene (PP) microporous filter membrane to complete the preparation of the photoresist.

[0132] The prepared photoresist is used as follows:

[0133] Spin coating was performed on a 4-inch silicon wafer, followed by pre-baking at 100°C for 3 minutes, and then exposure was performed in an LED 365nm contact exposure machine with an exposure energy of 200mJ / cm2, and then post-baking was performed at 70°C for 3 minutes, and then development was performed, wherein the development time was 1 minute, and the developer used was a tetramethylammonium hydroxide aqueous solution with a concentration of 2.38%.

[0134] The photolithographic pattern is obtained as Figure 6 As shown, the film thickness is 10.5 μm, and the cracking of the coating film is observed by optical developing microscope OM. The specific results are shown in Table 1.

[0135] The cracking results of the photoresist patterns of the above-mentioned Examples 1 to 5 and Comparative Example 1 are shown in Table 1. Figure 1 , Figure 3 , Figure 4 , Figure 5 and Figure 6 It can be seen that after adding a cross-linking agent to the chemically amplified positive UV photoresist of the present application, the cracking defect of the film is significantly improved, especially the cracking defect of the thick film (10 to 30 μm).

[0136] Table 1

[0137]

[0138] The above description of the embodiments is to facilitate those of ordinary skill in the art to understand and apply the present application. It is obvious that those familiar with the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without having to pay creative labor. Therefore, the present application is not limited to the embodiments herein, and improvements and modifications made by those skilled in the art based on the contents disclosed in the present application without departing from the scope and spirit of the present application are within the scope of the present application.

Claims

1. A chemically amplified positive ultraviolet photoresist, characterized in that: The photoresist comprises the following components in percentage by mass: The poly(p-hydroxystyrene) polymer resin comprises a first poly(p-hydroxystyrene) polymer resin and a second poly(p-hydroxystyrene) polymer resin; the mass percentage of the first poly(p-hydroxystyrene) polymer resin is 5-15%, and the mass percentage of the second poly(p-hydroxystyrene) polymer resin is 20-30%; The first poly(p-hydroxystyrene) polymer resin includes a first poly(p-hydroxystyrene) and / or a derivative of the first poly(p-hydroxystyrene), wherein the first poly(p-hydroxystyrene) is a copolymer of p-hydroxystyrene, styrene and tert-butyl acrylate, and the derivative of the first poly(p-hydroxystyrene) includes one or more of a tert-butyloxycarbonyl-protected first poly(p-hydroxystyrene), a tert-butyl-protected first poly(p-hydroxystyrene), an acetal-protected first poly(p-hydroxystyrene) and a ketal-protected first poly(p-hydroxystyrene); The second poly-p-hydroxystyrene polymer resin is a copolymer of p-hydroxystyrene, styrene and p-methoxystyrene.

2. The chemically amplified positive ultraviolet photoresist according to claim 1, characterized in that: The photoresist further comprises at least one of the following technical features: 1a) the first poly(p-hydroxystyrene) polymer resin is ST25 from Jiangsu Handuo Optical Materials Co., Ltd.; 1b) the weight average molecular weight of the first poly(p-hydroxystyrene) polymer resin is 20,000 to 30,000; 1c) the molecular weight distribution coefficient of the first poly(p-hydroxystyrene) polymer resin is 1.5 to 3.5; 1d) the second poly(p-hydroxystyrene) polymer resin is S601 from Jiangsu Handuo Optical Materials Co., Ltd.; 1e) the weight average molecular weight of the second poly(p-hydroxystyrene) polymer resin is 6000 to 18000; 1f) The molecular weight distribution coefficient of the second poly(p-hydroxystyrene) polymer resin is 1.5 to 2.

5.

3. The chemically amplified positive ultraviolet photoresist according to claim 1, characterized in that: The photoresist further comprises at least one of the following technical features: 2a) the photoacid generator is at least one selected from N-hydroxynaphthoimide trifluoromethanesulfonic acid, (4,8-dihydroxy-1-naphthyl)dimethylsulfonium trifluoromethanesulfonate, (4,7-dihydroxy-1-naphthyl)dimethylsulfonium trifluoromethanesulfonate, (4-methoxynaphthyl)diphenylsulfonium trifluoromethanesulfonate, (4-phenylthiophenyl)diphenylsulfonium trifluoromethanesulfonate, 2-(benzo[d][1,3]dioxolan-5-yl)-4,6-bis(trichloromethyl)-1,3,5-triazine, 2-(2,4-dimethoxyphenyl)-4,6-bis(trichloromethyl)-1,3,5-triazine and 2-[4-(4-methoxyphenyl)phenyl]-4,6-bis(trichloromethyl)-1,3,5-triazine; 2b) the acid quencher is at least one selected from triethylamine, tributylamine, trioctylamine and tri(3,6-dioxaheptyl)amine; 2c) the cross-linking agent is selected from at least one of diethylene glycol divinyl ether, tetramethoxymethyl glycoluril and hexamethoxymethyl melamine; 2d) the leveling agent is selected from at least one of 3M fluorocarbon surfactant FC-4430 and Troysol S366; 2e) the solvent is selected from at least one of anisole, toluene, xylene, trimethylolbenzene, chlorobenzene, dichlorobenzene, propylene glycol monoacetate, propylene glycol methyl ether acetate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, diethylene glycol methyl ether, diethylene glycol ethyl ether, diethylene glycol methyl ethyl ether, butyl acetate, neopentyl acetate, methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, cyclohexanone, diacetone alcohol, gamma-butyrolactone and ethyl lactate.

4. A method for preparing a chemically amplified positive ultraviolet photoresist as claimed in any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: mixing the poly(p-hydroxystyrene) polymer resin, the photoacid generator, the acid quencher, the crosslinking agent, the leveling agent and the solvent in proportion to obtain the chemically amplified positive ultraviolet photoresist.

5. The method for preparing a chemically amplified positive ultraviolet photoresist as claimed in claim 4, characterized in that: After all the raw materials are mixed, the preparation method includes filtering.

6. The method for preparing a chemically amplified positive ultraviolet photoresist according to claim 5, characterized in that: The filter pore size is 1 to 5 μm.

7. A method for using the chemically amplified positive ultraviolet photoresist as claimed in any one of claims 1 to 3, characterized in that: The method of use comprises the following steps: The chemically amplified positive ultraviolet photoresist is coated on a silicon wafer, and sequentially subjected to pre-baking, exposure, post-baking and development to obtain a photolithographic pattern.

8. The method for using the chemically amplified positive ultraviolet photoresist as claimed in claim 7, characterized in that: The method of use also includes at least one of the following technical features: 3a) The pre-baking temperature is 70-130°C; 3b) Pre-baking time is 3 to 7 minutes; 3c) The exposure machine used for the exposure is an LED 365nm contact exposure machine; 3d) Exposure energy is 200~500mJ / cm 2 ; 3e) post-baking temperature is 70-130°C; 3f) Post-baking time is 1 to 3 minutes; 3g) the developing solution used in the developing comprises tetramethylammonium hydroxide; 3h) The development time is 1 to 5 minutes.